Killing the witches : the horror of Salem, Massachusetts - O'Reilly, Bill; Dugard, Martin (O'Reilly, Bill. Killing series., 2023)
"With over 19 million copies in print and a remarkable record of #1 New York Times, Wall Street Journal, USA Today, and Publishers Weekly bestsellers, Bill O'Reilly's Killing series is the most popular series of narrative histories in the world. Killing the Witches revisits one of the most frightening and inexplicable episodes in American history: the events of 1692 and 1693 in Salem Village, Massachusetts. What began as a mysterious affliction of two young girls who suffered violent fits and exhibited strange behavior soon spread to other young women. Rumors of demonic possession and witchcraft consumed Salem. Soon three women were arrested under suspicion of being witches--but as the hysteria spread, more than 200 people were accused. Thirty were found guilty, twenty were executed, and others died in jail or their lives were ruined. What really happened in Salem? Killing the Witches tells the horrifying story of a colonial town's madness, offering the historical context of similar episodes of community mania during that time, and exploring the evidence that emerged in the Salem trials, in contemporary accounts, and in subsequent investigations. The result is a compulsively readable book about good, evil, and how fear can overwhelm fact and reason"--